Wi-Amp Wireless GSM, GPRS and HSDPA repeater amplifier - Espineda, Chanda G.
This project aims to rebroadcast GSM and HSDPA signals to areas with almost no cellular coverage at a minimal cost. The repeater system is consists of six modules - one for uplink and downlink operation for each system. Each module consists of a low noise amplifier, power amplifier and bandbass filter in cascade. The blocks were tested individually and then integrated. Impedance matching networks were designed and implemented using S-parameter data obtained from a Vector Network Analyzer (VNA). The GSM 900, DCS 1800 and HSDPA repeaters have a typical gain of 35 dB, 25 dB and 10dB gain respectively. System testing was performed using a spectrum analyzer and signal generator inside a Faraday cage. Functional tests confirm that both the GSM 900 and DCS1800 repeater system was able to extend radio coverage of cellular networks in an indoor test area that was previously out of reach of cellular service. However, the HSDPA repeater system was not able to extend radio coverage within the Faraday cage due to its relative lower gain with respect to the former two systems.